Reliability and Validity of Composite Scores from the NIH Toolbox Cognition Battery in Adults. (24th June 2014) - Heaton, Robert K.; Akshoomoff, Natacha; Tulsky, David; Mungas, Dan; Weintraub, Sandra; Dikmen, Sureyya; Beaumont, Jennifer; Casaletto, Kaitlin B.; Conway, Kevin; Slotkin, Jerry; Gershon, Richard
Abstract This study describes psychometric properties of the NIH Toolbox Cognition Battery (NIHTB-CB) Composite Scores in an adult sample. The NIHTB-CB was designed for use in epidemiologic studies and clinical trials for ages 3 to 85. A total of 268 self-described healthy adults were recruited at four university-based sites, using stratified sampling guidelines to target demographic variability for age (20–85 years), gender, education, and ethnicity. The NIHTB-CB contains seven computer-based instruments assessing five cognitive sub-domains: Language, Executive Function, Episodic Memory, Processing Speed, and Working Memory. Participants completed the NIHTB-CB, corresponding gold standard validation measures selected to tap the same cognitive abilities, and sociodemographic questionnaires. Three Composite Scores were derived for both the NIHTB-CB and gold standard batteries: "Crystallized Cognition Composite, " "Fluid Cognition Composite, " and "Total Cognition Composite" scores. NIHTB Composite Scores showed acceptable internal consistency (Cronbach's alphas=0.84 Crystallized, 0.83 Fluid, 0.77 Total), excellent test–retest reliability (r: 0.86–0.92), strong convergent (r: 0.78–0.90) and discriminant (r: 0.19–0.39) validities versus gold standard composites, and expected age effects (r=0.18 crystallized, r=−0.68 fluid, r=−0.26 total). Significant relationships with self-reported prior school difficulties and current health status, employment, and presence of a disability provided evidence of external validity. The NIH Toolbox Cognition Battery Composite Scores have excellent reliability and validity, suggesting they can be used effectively in epidemiologic and clinical studies. (JINS, 2014, 20, 1–11)